Oseointegración: una cascada de eventos - Arismendi-E., Jorge A.; Ospina-M., Ana María; Agudelo-A., Lina P. (Revista Facultad de Odontología Universidad de Antioquia, 2009)
This re view presents an update about biocompatibility, titanium and cellular and molecular events related healing alter en implanf placement in mandibular and maxilar bone. The terms biotolerent, bioinert, bioective, biointegretion, bioacceptability are discussed. Titanium and its cherecteristics are established to make it the choice as a material for dental implants and to explain how it is possible to get the osseointegration with them. Cellular events let us take a look at the osteoblast as a controllable determinant of bone formation for osseointegration. Alter implant lixation, molecular events during first 10-60 seconds are presented as main factors to get normal healing eround a foreign body. This inlormation indicates that knowledge of these cellular and molecular events will be useful to improve dental implant success and to expend their use in bone-deiicient sites.